Ekosistem organizacij v dobi digitalizacije: konferenčni zbornik - Marina Bajić; Šprajc, Polona; Podbregar, Iztok; Maletič, Damjan; Radovanović, Mirjana (2019)
Ecosystem of Organizations in the Digital Age: Conference Proceedings / 38th International Conference on Organizational Science Development. The technology is the key enabler of the development. It stimulates different areas of organizations and changes the established business in terms of digital. The ecosystem of organizations interwines with the basic cell of society through various layers of individuals, society, national and global layers. It provides a basis for survival and sustainability. The life of employees, organizations and the society in general is changing positively due to cultural, social and economic changes, influenced with digital technology. Integrating organizations into ecosystems is the way to complex connections that create opportunities for long-term integration and the power of organizations. Organizational sciences introduce new principles for sustainable development and connection of human and technology by focusing on innovative actions supporting diverse organizations and establishing ecosystems as business models. The 38th International Conference on Organizational Science Development in 2019 brings a new impetus to the perception of an individual as an essential member of organizations as well as the technology that promotes the development of various aspects of digital transformation. Digital-supported employees, digitally-enabled work and digital technology support create new trends in organizations, while returning to the essence of their operation – the ecosystem as a paradigm of networking and linking individuals and organizations.
Keywords: ecosystem; organizational sciences; digitalization; sustainability; international conference